226k views
2 votes
What is the intermediate step in the form (x + a)2 = b as a result of

completing the square for the following equation?
-3x2 - 36x = 300

1 Answer

0 votes

Answer:

we need to add a²=6² to both sides of
x^2+12x+6^2=-100+6^2 in order to rewrite in the form
\left(x\:+\:a\right)^2\:=\:b.

Explanation:

Given the equation


-3x^2-36x=300

First of all, we need to divide both sides by -3 to simplify it

i.e.


(-3x^2-36x)/(-3)=(300)/(-3)


x^2+12x=-100

In order to rewrite in the form
\left(x\:+\:a\right)^2\:=\:b, we need to add a²=6² to both sides


x^2+12x+6^2=-100+6^2

so


\left(x+6\right)^2=-64

Therefore, we need to add a²=6² to both sides of
x^2+12x+6^2=-100+6^2 in order to rewrite in the form
\left(x\:+\:a\right)^2\:=\:b.

User Sugan Pandurengan
by
4.6k points